CATCH RATE FLUCTUATIONS OF SKIPJACK AND OTHER TUNA RESOURCES IN THE NORTHERN WATERS OF ACEH - Badrudin Badrudin; Sofri Bahar (Indonesian Fisheries Research Journal, 1997)
The most dominant species of the ''large pelagic group" landed in Lampulo, Aceh,were skipjack, yellowfin tuna and small tuna. Thcse fish were caught by mini purse seine through fishing activities carried out on a dailv basis.